2016
DOI: 10.1111/ggi.12758
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease‐related physical frailty and cognitive impairment: a systemic review

Abstract: Chronic kidney disease is a potential cause of frailty and cognitive impairment. Vascular and non-vascular factors are the possible causes. The mechanism of chronic kidney disease-induced physical frailty and cognitive impairment suggests that multidimensional interventions may be effective therapeutic strategies in the early stage of chronic kidney disease. Geriatr Gerontol Int 2017; 17: 529-544.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 161 publications
(317 reference statements)
0
46
0
10
Order By: Relevance
“…Several reviews have been published on the well‐established association of chronic kidney disease and cognitive dysfunction; yet, they have focused on advanced kidney damage stages . Presence of microalbuminuria, mainly attributed to glomerular leakage, corresponds to an earlier subclinical time‐point in kidney disease progress, when eGFR may have not yet been affected .…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews have been published on the well‐established association of chronic kidney disease and cognitive dysfunction; yet, they have focused on advanced kidney damage stages . Presence of microalbuminuria, mainly attributed to glomerular leakage, corresponds to an earlier subclinical time‐point in kidney disease progress, when eGFR may have not yet been affected .…”
Section: Discussionmentioning
confidence: 99%
“…3 One review suggested that CKD is a risk factor for cognitive impairment and frailty in older adults. 4 The incidence of frailty in patients with chronic kidney disease is higher than that in the general elderly population due to changes in protein metabolism, inflammation, oxidative stress, anemia and other reasons. 5 It has been pointed out that the incidence of frailty in the healthy elderly is about 11%, while the incidence of frailty in the elderly with CKD is about 6 times (up to 60%) as that in the healthy elderly.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review was performed looking at the relationship between CKD and physical frailty and cognitive impairment (38). They found clear evidence of a relationship between CKD and frailty and cognitive impairment.…”
Section: Sarcopeniamentioning
confidence: 99%